2015
DOI: 10.1007/s00371-015-1091-1
|View full text |Cite
|
Sign up to set email alerts
|

Learning best views of 3D shapes from sketch contour

Abstract: In this paper, we introduce a novel learningbased approach to automatically select the best views of 3D shapes using a new prior. We think that a viewpoint of the 3D shape is reasonable if a human usually draws the shape from it. Hand-drawn sketches collected from relevant datasets are used to model this concept. We reveal the connection between sketches and viewpoints by taking context information of their contours into account. Furthermore, a learning framework is proposed to generalize this connection which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Contour rendering. Recent studies [27,28] present a hybrid line rendering method to generate 2D contour maps for 3D shapes and obtain good performance. In this paper, we adopt this approach which combines predefined exterior silhouettes, occluding contours, suggestive contours [29] and shape boundaries to generate the final contour map from a given view point for further editing.…”
Section: Contour-based Face Model Refinementmentioning
confidence: 99%
“…Contour rendering. Recent studies [27,28] present a hybrid line rendering method to generate 2D contour maps for 3D shapes and obtain good performance. In this paper, we adopt this approach which combines predefined exterior silhouettes, occluding contours, suggestive contours [29] and shape boundaries to generate the final contour map from a given view point for further editing.…”
Section: Contour-based Face Model Refinementmentioning
confidence: 99%
“…Another approach conducted a simple, statistical analysis of a high volume of internet photos in order to directly determine the canonical views [HO05, MW12]. In addition, [ZLJW15] demonstrated that the semantic viewpoints can be trained even by hand drawings.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, the selected salient views do not always correspond to our common knowledge of the objects. The other approaches [FCODS08, MS09, LZH12, ZLJW15] study some high‐level measurements in seeking meaningful information, but generalization of the hand‐designed features is not always straightforward for more sophisticated cases.…”
Section: Introductionmentioning
confidence: 99%
“…This can eliminate the negative interference of the bad viewpoint image for our retrieval results. This method is adopted by Zhao et al [25] to acquire the best-view images of a model. Here, we only want to get the good view images, not best-view image.…”
Section: Svm Classifiermentioning
confidence: 99%